Flying witch. 4 - Ishizuka, Chihiro (Vertical Comics, 2017)
Witch-in-training Makoto shops for a new robe for herself and Chinatsu; combines her studies with witchcraft to make a treat; and visits the beach with Inukai where they meet a mysterious creature.